Prescribing trends of inhaler treatments for asthma and chronic obstructive pulmonary disease within a resource-constrained environment in the Scottish national health service: findings and implications. (3rd July 2019) - McCabe, Holly; Godman, Brian; Kurdi, Amanj; Johnston, Katie; MacBride-Stewart, Sean; Lennon, Janey; Hurding, Simon; Bennie, Marion; Morton, Alec
ABSTRACT: Background : There is an increasing prevalence of asthma and chronic obstructive pulmonary disease (COPD) worldwide, leading to increased inhaler use. However, there are concerns with inhaler compliance resulting in different patented inhalers and longer-acting formulations. As a result, inhalers are now among the highest expenditure items in ambulatory care in Scotland leading to multiple initiatives to keep within budget without compromising care. Method : This study assesses inhaler utilization and expenditure between 2001 and 2017 alongside health authority initiatives. Results : There was an increase by 137% in inhaler utilization between 2001 and 2017, and a two-fold increase in expenditure, driven by the increasing use of patented combination inhalers to address concerns. This is very different to the oral markets where expenditure on proton pump inhibitors, statins, and antihypertensives have fallen considerably recently despite increased volumes due to the increasing use of low-cost generics. However, inhaler expenditure has started to fall with an increasing use of lower cost combinations and initiatives to reduce the steroid burden alongside monitoring patient care. Conclusion : Challenges with using and changing inhalers has meant this market has not followed other high-volume drug classes following patent loss. This is starting to change, with the situation monitored to enhance efficient prescribing alongside continued good quality care.